The features of the nitric oxide system in the left ventricle myocardium in the rats with experimental intermittent hypoxia of different duration - Kolesnyk, Yu. M.; Isachenko, M. I.; Melnikova, O. V.; Колесник, Юрій Михайлович; Ісаченко, Марія Ігорівна; Мельнікова, Ольга Валеріївна; Колесник, Ю. М.; Исаченко, М. И.; Мельникова, О. В. (Запорізький державний медичний університет, 2019)
The aim was to determine the features of the NO system status in the left ventricular myocardium in the rats with intermittent hypoxic hypobaric hypoxia during 15 and 60 days. Material and methods. The study was conducted on the 30 Wistar male rats, which were divided into 3 experimental groups: the 1st – control, the 2nd – rats exposed to intermittent hypoxia during 15 days and the 3rd group – the rats exposed to intermittent hypoxia during 60 days. Blood pressure was measured in all the rats. The objects and methods of the study were blood plasma (nitrotyrosine detection with immunoassay) and the myocardium of the left ventricle (concentration of nitrites by Griess nitrite test and content of immunoreactive material to the nitric oxide synthase isoforms by immunofluorescence method). mRNA expression of NOS isoforms was determined by PCR-RT method in the myocardium. Results. In the rats with 15-day hypoxia there was an increase in systolic pressure compared to control, and in 60-day hypoxia, there was also an increase in diastolic pressure although this changes were within the normotensive range. mRNA to all the myocardial NOS isoforms was characterized by an increase in both hypoxia groups. At the same time, the indices of the immunoreactive material content to the NOS isoforms were dependent on the hypoxia term. The concentration of the nitrotyrosine increased in both hypoxic groups, but in the long term it occurred along with a decrease in the level of nitrite, which indicates the possibility of nitro-oxidative stress. Conclusions. The 15-day intermittent hypoxia changes the myocardial NO system: an increase in the expression of all 3 isoforms, an increase in the nitrite and the nitrotyrosine content. iNOS becomes the predominant form of the enzyme in the myocardium with the increasing its mRNA. In 60-day hypoxia, the profile of the NOS enzyme is characterized by increased expression of the constitutive isoforms and decreased inducible NOS expression that was accompanied with significant increase in mRNA of all three forms. The level of terminal metabolites of NO was characterized by a decrease in the nitrite while the content of the nitrotyrosine increased. Мета роботи – встановити особливості стану системи NO в міокарді лівого шлуночка щурів при переривчастій гіпоксичній гіпобаричній гіпоксії тривалістю 15 і 60 днів. Матеріали та методи. Дослідження здійснили на 30 щурах-самцях лінії Wistar, яких поділили на 3 експериментальні групи: 1 – контрольна, 2 – щури, які зазнавали впливу переривчастої гіпоксії протягом 15 днів, 3 група – щури з гіпоксією протягом 60 днів. Усім щурам вимірювали артеріальний тиск. Об’єкти дослідження – плазма крові, в якій імуноферментним методом визначали концентрацію нітротирозину, та міокард лівого шлуночка, в якому біохімічним методом Грісса досліджували концентрацію нітритів, імунофлуоресцентним методом визначали вміст імунореактивного матеріалу до ізоформ синтази оксиду азоту. Також у міокарді методом ПЛР-РЧ визначали експресію мРНК до ізоформ NOS. Результати. Хоча показники АТ у щурів із гіпоксією перебувають у нормотензивних межах, у групах із гіпоксією спостерігали збільшення систолічного тиску порівняно з контролем, а при 60-денній гіпоксії – збільшення і діастолічного тиску. мРНК до всіх ізоформ у міокарді характеризувалась збільшенням в обох групах із гіпоксією. Показники вмісту імунореактивного матеріалу до ізоформ NOS змінювалися не так однозначно й мали залежність від терміну гіпоксії. Концентрація нітротирозину збільшилась в обох гіпоксичних групах, але при тривалій гіпоксії це відбулося на тлі зменшення рівня нітритів, що дає змогу припустити розвиток нітрозооксидативного стресу. Висновки. 15-денна переривчаста гіпоксія призводить до зміни міокардіального ізоформного профілю NOS, збільшення показників експресії всіх трьох ізоформ, підвищення вмісту нітритів і нітротирозину. Переважною формою ферменту в міокарді стає іNOS на тлі збільшення її мРНК. При 60-денній гіпоксії профіль ферменту NOS характеризується збільшенням експресії конститутивних ізоформ і зниженням індуцибельної ізоформи на тлі істотного підвищення мРНК усіх трьох форм. Рівень кінцевих метаболітів NO характеризується зниженням нітритів, але збільшенням вмісту нітротирозину. Цель работы – установить особенности состояния системы NO в миокарде левого желудочка крыс при прерывистой гипоксической гипобарической гипоксии продолжительностью 15 и 60 дней. Материалы и методы. Исследование проведено на 30 крысах-самцах линии Wistar, которых поделили на 3 экспериментальные группы: первая – контрольная, 2 – крысы, которые подвергались прерывистой гипоксии в течение 15 дней, 3 группа – крысы с гипоксией в течение 60 дней. Всем крысам измеряли артериальное давление. Объекты исследования – плазма крови, в которой иммуноферментным методом определяли концентрацию нитротирозина, и миокард левого желудочка, в котором биохимическим методом Грисса исследовали концентрацию нитритов, иммунофлуоресцентным методом определяли содержание иммунореактивного материала к изоформам синтазы оксида азота. Также в миокарде методом ПЦР-РЧ определяли экспрессию мРНК к изоформам NOS. Результаты. Хотя показатели АД у крыс с гипоксией находятся в нормотензивных пределах, в группах с гипоксией наблюдали увеличение систолического давления по сравнению с контролем, а при 60-дневной гипоксии – увеличение и диастолического. мРНК ко всем изоформам в миокарде характеризовалась увеличением в обеих группах с гипоксией. Показатели содержания иммунореактивного материала к изоформам NOS изменялись не так однозначно и имели взаимосвязь с продолжительностью гипоксии. Концентрация нитротирозина увеличилась в обеих гипоксических группах, но при длительной гипоксии это сопровождалось уменьшением уровня нитритов, что позволяет предположить развитие нитрозооксидативного стресса. Выводы. 15-дневная прерывистая гипоксия приводит к изменению миокардиального изоформного профиля NOS, увеличению показателей экспрессии всех трех изоформ, повышению содержания нитритов и нитротирозина. Преобладающей формой фермента в миокарде становится iNOS на фоне увеличения ее мРНК. При 60-дневной гипоксии профиль фермента NOS характеризуется увеличением экспрессии конститутивных изоформ и снижением индуцибельной изоформы на фоне повышения мРНК всех трех форм. Уровень конечных метаболитов NO характеризуется снижением нитритов и увеличением содержания нитротирозина.
Особливості системи оксиду азоту в міокарді лівого шлуночка щурів з експериментальною переривчастою гіпоксією різної тривалості
Особенности системы оксида азота в миокарде левого желудочка крыс с экспериментальной прерывистой гипоксией различной продолжительности
Keywords: nitric oxide synthase; NOS isoforms; left ventricle; heart; intermittent hypoxia; rats; Wistar; синтаза оксиду азоту; ізоформи синтази оксиду азоту; лівий шлуночок серця; переривчаста гіпоксія; щури лінії Wistar; синтаза оксида азота; изоформы синтазы оксида азота; левый желудочек сердца; гипоксия; крысы линии Wistar